Dynamic Characteristics of a Cylindrical Roller Bearing with Cage Cracks - Yang Yang; Xiaoye Qi; Yongjie Wang; Meiling Wang; Baogang Wen; Jingyu Zhai (Lubricants)
Cracks in the cages of bearings frequently appear during manufacturing and operation, directly affecting the dynamic characteristics and reliability of the bearing. A dynamic model of a cylindrical roller bearing with cage cracks was established, in which the interactions between the cage, the roller and rings, and the oil-gas lubrication effects were considered to investigate the influence of cracks. The derived dynamic differential equations of cylindrical roller bearings were solved by means of the modified Newton–Raphson iterative algorithm and the BDF predictive correction algorithm with automatic variable order and step length. The dynamic characteristics of bearings with different cage cracks were studied, and the influence of cage cracks on bearing dynamic characteristics and cage life was analyzed. The results show that the effect of crack depth, angle, and location on bearing dynamics and crack propagation life is obvious. With the increase in crack depth and angle, the cage equivalent stress changes obviously, and the movement of the cage’s centroid is chaotic. The propagation life of crack initiation on the side beam is much smaller than that of crack initiation on the beam.